Unsolved problems in ecology - Dobson, Andrew; Holt, Robert D.; Tilman, David, 1949- (Princeton University Press, 2020)
"This volume provides a series of essays on open questions in ecology with the overarching goal being to outline to the most important, most interesting or most fundamental problems in ecology that need to be addressed. The contributions span ecological subfields, from behavioral ecology and population ecology to disease ecology and conservation and range in tone from the technical to more personal meditations on the state of the field. Many of the chapters start or end in moments of genuine curiosity, like one which takes up the question of why the world is green or another which asks what might come of a thought experiment in which we "turn-off" evolution entirely"--